Rationality and the problem of primeval mind - Kurpanik, Szymon (Folia Philosophica, 2011)
The paper discusses the relation between the Western concept of rationality and what we know about primeval mind from anthropology and ethnology, what might be found important for scholars working on the problems of mind and rationality. The author discusses both the perspectives of the search for the links between Western form of rationality and archaic mind and some controversies concerning this search.